Evaluasi Penerimaan Aplikasi Mobile Among Warga Smart City Pemerintah Kota Batu Menggunakan Model UTAUT - Muhammad Arsy Uber Jayaprana; Widhy Hayuhardhika Nugraha Putra; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The Among Warga Mobile Application is one of the products of Batu Smart City e-government service that is useful for reporting on public facilities issues in Batu City which can be accessed anytime and anywhere via an Android-based smartphone. The purpose of this study is to describe the level of acceptance of applications based on the variable Performance Expectancy, Effort Expectancy, Facilitating Conditions, Social Influence, Trust of the Internet, Trust of Government, Trust of CSC, and Positive Intention to Use E-Government Services, and give recommendations to increase the acceptance and use of Among Warga applications in Batu City Government. The model used in this study is the modified UTAUT (Unified Theory of Acceptance and Use of Tehcnology). This study uses a qualitative approach where data collection is obtained by conducting interviews with open questions to the speakers who are application users who have reported on the application. The sampling technique in this study was purposive sampling and then carried out a qualitative analysis of the findings and collection of research data. The results obtained based on this study shown that a person's intention in adopting the Among Warga application is based on the eight variables, the majority of which have quite good results because this application has the benefit such reporting become easier, easy to use and to be learned.